Case Report: The First Report of NUP214-ABL1 Fusion Gene in Acute Myeloid Leukemia Patient Detected by Next-Generation Sequencing - Wang, Huan-Ping; He, Jun-Jun; Zhu, Qiao-Yun; Wang, Lin; Li, Jian-Hu; Huang, Jian-Song; Xie, Wan-Zhuo; Zhu, Hong-Hu; Jin, Jie (Frontiers in Oncology, 2021)
The NUP214-ABL1 fusion gene is a constitutively active tyrosine kinase that can be detected in 6% of T-cell acute lymphoblastic leukemia (T-ALL) patients, and it can also be found in B-cell acute lymphoblastic leukaemia (B-ALL). However the NUP214-ABL1 fusion in acute myeloid leukemia (AML) has not yet been reported. Up to now, the sensitivity of NUP214-ABL1-positive patients to tyrosine kinase inhibitor (TKI) is still controversial. Here we report the first case of an AML patient carrying NUP214-ABL1 fusion gene. The conventional AML chemotherapy regimen for the patient was successful. Identification of additional AML patients with NUP214-ABL1 fusion gene will provide treatment experience and prognostic evaluation.